(untitled) (Revista Brasileira Multidisciplinar, 2023)
This work aims to report a case of aspergillosis in 49-day-old broilers. The case occurred in a commercial broiler farm of multiple ages located in the metropolitan region of Fortaleza. Respiratory problems, unresponsive to antibiotics were observed in broilers during the rearing period. Given the high morbidity and mortality, birds were taken for necropsy, 10 birds with recent death and 5 birds with respiratory symptoms were sacrificed. At necropsy, discharge and a yellowish nodular focal area in the nasal cavity, opacity and thickening of air sacs and presence of yellowish caseous material were observed. Histopathological examination revealed a multifocal infiltration of histiocytes and heterophils in the submucosa, in addition to foci of epithelial necrosis. In the air sacs, foci of histiocytic infiltration were observed, some associated with a central area of necrosis containing negative images of hyphae (compatible with Aspergillus sp.). In view of the association of the birds’ respiratory condition with the necropsy and histopathological findings, granulomatous airsacculitis associated with fungal hyphae was diagnosed, suggestive of aspergillosis.